Cyber Victimization and Depression Among Adolescents With Intellectual Disabilities and Developmental Disorders: The Moderation of Perceived Social Support. Issue 2 (3rd April 2017) - Wright, Michelle F.
ABSTRACT: The aim of this study was to examine the mitigating effect of perceived social support from parents, teachers, and friends on the association between cyber victimization and depression, accessed one year later. Adolescents ( n = 131; 13–15 years old; 73% male) with intellectual and developmental disabilities completed questionnaires on their face-to-face and cyber victimization, perceived social support, and depression in 7th grade (Time 1). They also completed the depression questionnaire one year later in the 8th grade (Time 2). The findings suggested that high levels of Time 1 perceived social support from parents and teachers weakened the relationship between Time 1 cyber victimization and Time 2 depression, while controlling for Time 1 face-to-face victimization and Time 1 depression. The results are discussed in regard to the supportive roles of parents and teachers in adolescents' lives. Recommendations are made for programs to consider including adolescents with intellectual disabilities and developmental disorders in prevention and intervention programs.